Prenatal multiple micronutrient-fortified balanced energy-protein supplementation and newborn telomere length and mitochondrial DNA content: a randomized controlled efficacy trial in rural Burkina Faso - Giles T. Hanley-Cook; Yuri Bastos-Moreira; Dries S. Martens; Trenton Dailey-Chwalibóg; Laeticia Celine Toe; Brenda de Kok; Lionel OIivier Ouédraogo; Alemayehu Argaw; Kokeb Tesfamariam; Patrick Kolsteren; Lieven Huybregts; Tim S. Nawrot; et al. (Food Science and Human Wellness)
BackgroundEvidence regarding the effectiveness of prenatal nutritional supplements has mainly considered anthropometric pregnancy outcomes. The effect on markers of health and disease, such as offspring telomere length (TL) and mitochondrial DNA content (mtDNAc) is unknown.ObjectivesWe assessed the efficacy of maternal multiple micronutrient (MMN)-fortified balanced-energy protein (BEP) and iron-folic acid (IFA) supplementation on newborn TL as a secondary outcome and mtDNAc as a non-declared outcome.DesignWe conducted a randomized controlled trial in rural Burkina Faso, among pregnant females (15-40 years old) enrolled at < 21 weeks of gestation. Mothers received either MMN-fortified BEP and IFA (intervention) or IFA only (control) throughout pregnancy. Whole arterial blood samples were collected from the umbilical cord of 104 control and 90 intervention group infants, respectively. Average relative TL and mtDNAc were measured using quantitative polymerase chain reaction. Linear regression models were fitted to assess TL and mtDNAc differences across trial arms.ResultsWe found that a combined daily MMN-fortified BEP supplement and IFA tablet did not affect newborn TL [β =-0.010 (95% CI:-0.057, 0.036); P = 0.662] or mtDNAc [β = 0.065 (95% CI:-0.203, 0.073); P = 0.354], as compared to an IFA tablet alone. These findings were confirmed (P > 0.05) by adjusting the regression models for potential prognostic factors of study outcomes at enrollment. Exploratory analyses indicated higher, but non-significantly different mtDNAc among children born either small-for-gestational age, low birthweight, or preterm.ConclusionNewborns from mothers who received daily nutritional supplements across gestation did not have different relative TL or mtDNAc.